“IMPACT OF PERCEIVED ORGANIZATIONAL SUPPORT & EMOTIONAL INTELLIGENCE ON EMPLOYEES’ PERFORMANCE OF BANKING SECTOR IN REWA REGION" (International Journal of Food and Nutritional Sciences, 2022)
The research in its course will look into the forms of transactional and transformational theories of leadership. In addition it will also explore the domains of employee’s organizational behavior, job satisfaction of professional and the concept of organizational support. All these aspects are in close relativity which the organizational behavior of an employee. In its scope this research will also look into the areas of job satisfaction of employees and that of organizational support which will be in relation to the leadership styles of transactional and transformational guidance and the organizational citizenship behavior of the employees of a company. It will be clearly pointed out that the ability to understand our own feelings and the other people who are around us and to manage our own emotions can help to improve the performance of employees in a big way and also their commitment to the company. the research in its course will point out that emotional intelligence is very important to predict a person's organizational commitment and assess their performance at their work in this context managing a person's emotions is very important.